Tending Iowa's Land : Pathways to a Sustainable Future - Mutel, Cornelia Fleischer (Book collections on Project MUSE., 2022)
"An Introduction to Iowa's Environmental Problems is an edited volume with 17 contributors besides Connie Mutel herself-all Iowa authors who are scientific experts in the field. Geared toward course adoption in Iowa and Midwest classrooms, it will fill a need for a comprehensive, but accessible and brief overview of the environmental issues Iowa faces, and what we can do about them. Specifically, the volume breaks down the issues surrounding Iowa's land and soils, water, atmosphere, and loss of biological diversity. Teachers lack a go-to resource for explaining this topic to their students, and many Iowans remain unaware of the environmental impacts of farming. And with the new administration's focus on environmental concerns, including climate change, the timing is right to change that. At this point, Iowa can choose a route toward becoming an agricultural factory that disregards nature's sustainability and resilience, or we can steer toward a saner future that recognizes and honors our soils, climate, water, and native species. With this book, Mutel will help guide future Iowa leaders toward the latter"--